Smart Cellulose-Based Janus Fabrics with Switchable Liquid Transportation for Personal Moisture and Thermal Management - Xi, Jianfeng; Lou, Yanling; Meng, Liucheng; Deng, Chao; Chu, Youlu; Xu, Zhaoyang; Xiao, Huining; Wu, Weibing (Nano-Micro Letters, 2024)
The Janus fabrics designed for personal moisture/thermal regulation have garnered significant attention for their potential to enhance human comfort. However, the development of smart and dynamic fabrics capable of managing personal moisture/thermal comfort in response to changing external environments remains a challenge. Herein, a smart cellulose-based Janus fabric was designed to dynamically manage personal moisture/heat. The cotton fabric was grafted with N-isopropylacrylamide to construct a temperature-stimulated transport channel. Subsequently, hydrophobic ethyl cellulose and hydrophilic cellulose nanofiber were sprayed on the bottom and top sides of the fabric to obtain wettability gradient. The fabric exhibits anti-gravity directional liquid transportation from hydrophobic side to hydrophilic side, and can dynamically and continuously control the transportation time in a wide range of 3–66 s as the temperature increases from 10 to 40 °C. This smart fabric can quickly dissipate heat at high temperatures, while at low temperatures, it can slow down the heat dissipation rate and prevent the human from becoming too cold. In addition, the fabric has UV shielding and photodynamic antibacterial properties through depositing graphitic carbon nitride nanosheets on the hydrophilic side. This smart fabric offers an innovative approach to maximizing personal comfort in environments with significant temperature variations. Highlights: 1 A smart all-cellulose Janus fabric was designed for personal moisture/thermal management. 2 The fabric can dynamically and continuously control the liquid transportation time in response to the temperature. 3 The fabric can accelerate the heat dissipation rate at high temperatures, while slow it down at low temperatures.